Forensic Evaluation of Abundance and Growth Indices of Carrion Insects from Rabbits Euthanized with Paraquat Dichloride Herbicide - Tyokumbur, Emmanuel; Olagunju , Oluwayanmife Ayomide (Sahel Journal of Life Sciences FUDMA, 2025)
A study was carried out on the forensic entomotoxicological evaluation of carrion insects of rabbits euthanized with Paraquat dichloride herbicide between September and October 2020 at University of Ibadan. The rabbits were euthanized with 200ml of Paraquat while the control group were scarified by cervical dislocation. Adult carrion insects were collected from the carrions using a sweep net and stored in 70% alcohol. Calliphoridae and Muscidae were the initial pioneers of the decomposing carcass and were seen during the fresh stage, while Sarcophagidae arrived shortly after the fresh stage of decomposition. The control group had more abundance and species composition of carrion insects than the Paraquat-poisoned rabbits. The length and weight of the larvae as indices of growth were also observed to be comparatively higher in the control. The highest mean temperature value for the decomposing 20ml Paraquat-treated rabbits was 30.45°C while its lowest mean value was 24.4°C. The highest mean relative humidity value was 96.5% while the least recorded was 67% due to the rainy season. Paraquat was found to retard the growth of carrion larva as shown in Musca domestica when compared with the control. It can be deduced from this study that carrion insects are essential in providing the essential ecosystem service of decomposition and can be used in solving suicide puzzles through the extrication of post mortem intervals in conjunction with environmental variables. More studies are therefore needed to test the specific effects of other commonly used suicide poisons on carrion insects in Nigeria.